Utilization of social media instagram @satgascovid19.id in fulfilling the need for information about Covid-19 (survey on the people of DKI Jakarta) - Prasetyo, Kurniawan; Amrullah, Haekal Fajri; Endri, Engga Probi (Penerbit Universiti Kebangsaan Malaysia, 2021)
At the end of 2019 the world was shocked by the presence of a new virus, namely the corona virus disease or better known as Covid-19. To deal with the Covid-19 case in Indonesia, the government formed a Covid-19 Response Task Force (Satgas). The socialization program carried out by the Covid 19 Task Force is the establishment of social media Instagram with the @ satgascovid19.id account as a medium to convey information. The formulation of the problem in this research is how the use of social media Instagram @ satgascovid19.id in meeting the information needs about covid-19 for the people of DKI Jakarta ?. The purpose of this study is to describe the use of social media Instagram @ satgascovid19.id in fulfilling the information needs about covid-19 for the people of DKI Jakarta. This study uses a quantitative approach with survey methods on the people of DKI Jakarta, amounting to 400 people. The results showed that the use of social media instagram @ satgascovid19.id was effective in meeting the information needs about covid-19 based on the interval value of the Likert Summated Rating , it was known where the respondent's score was against each statement submitted. The total score is 27828 in the range> Q2 to Q3 = effective. The level of effectiveness of the use of social media is measured through several measurement dimensions including: context, communication, collaboration, and connection. In addition, people have a preference for finding information about Covid-19 on social media Instagram compared to other media.